Participant, purpose, place: planning for content-area talk (New Jersery: Wiley Company, 2022)
How can you support your students' oral language development across the day? This article introduces the 3Ps Model (Participants, Purpose, and Place) as a framework for planning content-area talk in early childhood settings.